Method and Individual in Hobbes - Villaverde López, Guillermo (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
This paper aims at reconstructing the conception of the individual and the individuality that operates in Hobbes’s scientia civilis, and tries to show that this conception is a key element of that project. Firstly we rebuild Hobbes’s view of method, by means of which we proceed to his theory of individuality as the result of applying that method to the social phenomena. Secondly, we select some stretches in Hobbes argumentative path (especially from De Cive and Leviathan) and we intent to show that they rely on this conception of individuality in a way that every attempt of setting it aside would render the whole project incomprehensible. Throughout the paper we also try to define the relation between Hobbes and his theory of individuality and early modern political philosophy and early modern philosophy as such.